(untitled) (Scientific journal of the Fergana State University, 2024)
This article delves into the realm of publicistic style, analyzing its advantages and the strategic use of proverbs and sayings within this genre. Publicistic style, characterized by its persuasive and expressive nature, employs linguistic devices to influence and captivate its audience. Proverbs and sayings, being concise yet profound expressions of cultural wisdom, play a crucial role in enhancing the effectiveness of publicistic writing. This exploration sheds light on the significance of these elements in crafting compelling narratives and persuasive discourse.